E-Governance: Application and Challenges of the Local Governance Institutions of Northern Sri Lanka - Vijayakumar, N.; Velnampy, T.; Nimalathasan, B. (South Eastern University of Sri Lanka, 2024)
This study aims to evaluate the level of application of e-Governance methods in the local governance institutions of Northern Sri Lanka and to comprehend the challenges faced by them in accommodating e-Governance methods. The focus of this study is Northern Sri Lanka, a province earlier affected by the civil war and currently engaged in the post-war socio-economic development phase. An integrated approach has been adopted to identify the e-Governance applications used by the local governance government institutions and the challenges in accommodating E-governance. Key Informant interviews were conducted with important officials of the Northern provincial council including the 34 Local Authorities of the Northern province. Secondary data was compiled via an analysis of the relevant secondary data sources. There are 22 standalone E-Systems used by various public institutions of the Northern Provincial Council. Out of 22 systems, twelve are government to citizen services, nine are government to government services and one is government to business services. Out of 34 local authorities in the Northern province, only 23 are using a minimum of one or more e-governance applications. Eleven Local Authorities are not using any of the e-governance applications. The most commonly used e-governance system is the payroll Management system; 21 Local Authorities are using the payroll management system. The local governance institutions in the northern province are experiencing multidimensional challenges related to relevant policies, legislation, resources and readiness in implementing the e- governance application. They are presently at an elementary stage in accommodating e-governance.
Keywords: e-Governance; Local Government; Local Governance; Sri Lanka